Mannitol production from glycerol by resting cells of Candida magnoliae - Khan, Asiya; Bhide, Amey J.; Gadre, Ramchandra V. (Bioresource Technology, 2009)
Production of mannitol from glycerol by resting cells of Candida magnoliae under aerobic condition was investigated. The resting cells were Suspended in aqueous Solution of glycerol in Erlenmeyer flasks and incubated on rotary shaker. The samples were analyzed by ion exclusion-HPLC equipped with refractive index and UV detector. The resting cells of C. magnoliae produced mannitol from fructose, Sucrose and glycerol but not from glucose. Addition of yeast extract and/or potassium phosphate to the glycerol solution adversely affected its conversion to mannitol. The conversion of glycerol to mannitol was dependent on oxygen availability. Using testing cells, the yield of mannitol was as high as 45%. This is probably the first report of conversion of glycerol to mannitol by osmophilic yeast. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Candida magnoliae; Glycerol; Mannitol production; Resting cells

Amylase gene expression patterns in Helicoverpa armigera upon feeding on a range of host plants - Kotkar, Hemlata M.; Bhide, Amey J.; Gupta, Vidya S.; Giri, Ashok P. (Gene, 2012)
Expression of two amylase genes (HaAmy1 and HaAmy2) was studied in Helicoverpa armigera (Hubner; Lepidoptera: Noctuidae) feeding on different host plants and during larval development. Alignment of HaAmy1 and HaAmy2 with other insect amylases shows similarities with known Lepidopteran amylase transcripts. H. armigera amylase gene expression is influenced by the availability of reducing sugars, sucrose and starch content of host plants and further correlates to the pool of reducing sugars in the gut and haemolymph of larvae. HaAmy1 and HaAmy2 during larval development on two host plants viz., maize (cereal) and marigold (ornamental) showed their relative difference. Results support the view that when host plants differ in their macronutrients, relationships of enzymes and substrates are flexible. The present work highlights the distribution of HaAmy1 and HaAmy2 (i) during various stages of insect development (second, fourth and sixth instar, pupa, adult and egg), (ii) in various tissues viz., head, haemolymph, fat body, integument and whole larval body of H. armigera feeding on artificial diet and (iii) in three gut regions of larvae fed on various diets. Complexity in expression of amylase genes suggests existence of mechanisms involved to detect nutrient balance required for avoiding fitness costs and focus their importance in insect nutrition. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Diets; Digestive amylase; Gene expression; Helicoverpa armigera; Nutrition

Biosynthesis of antinutritional alkaloids in solanaceous crops is mediated by clustered genes - Itkin, M.; Heinig, U.; Tzfadia, O.; Bhide, Amey J.; Shinde, B.; Cardenas, Pablo D.; Bocobza, S. E.; Unger, T.; Malitsky, Sergey; Finkers, R.; Tikunov, Y.; Bovy, A.; et al. (Science, 2013)
Steroidal glycoalkaloids (SGAs) such as alpha-solanine found in solanaceous food plants-as, for example, potato-are antinutritional factors for humans. Comparative coexpression analysis between tomato and potato coupled with chemical profiling revealed an array of 10 genes that partake in SGA biosynthesis. We discovered that six of them exist as a cluster on chromosome 7, whereas an additional two are adjacent in a duplicated genomic region on chromosome 12. Following systematic functional analysis, we suggest a revised SGA biosynthetic pathway starting from cholesterol up to the tetrasaccharide moiety linked to the tomato SGA aglycone. Silencing GLYCOALKALOID METABOLISM 4 prevented accumulation of SGAs in potato tubers and tomato fruit. This may provide a means for removal of unsafe, antinutritional substances present in these widely used food crops.

Biochemical, structural and functional diversity between two digestive alpha-amylases from helicoverpa armigera - Bhide, Amey J.; Channale, Sonal M.; Patil, Sucheta S.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2015)
Background: Helicoverpa armigera (Lepidoptera) feeds on various plants using diverse digestive enzymes as one of the survival tool-kit. The aim of the present study was to understand biochemical properties of recombinant alpha-amylases of H. armigera viz., HaAmy1 and HaAmy2. Methods: The open reading frames of HaAmy1 and HaAmy2 were cloned in Pichia pastoris and expressed heterologously. Purified recombinant enzymes were characterized for their biochemical and biophysical attributes using established methods. Results: Sequence alignment and homology modeling showed that HaAmy1 and HaAmy2 were conserved in their amino acid sequences and structures. HaAmy1 and HaAmy2 showed optimum activity at 60 degrees C; however, they differed in their optimum pH. Furthermore, HaAmy2 showed higher affinity for starch and amylopectin whereas HaAmy1 had higher catalytic efficiency. HaAmy1 and HaAmy2 were inhibited to the same magnitude by a synthetic amylase inhibitor (acarbose) while wheat amylase inhibitor showed about 2-fold higher inhibition of HaAmy1 than HaAmy2 at pH 7 while 6-fold difference at pH 11. Interactions of HaAmy1 and HaAmy2 with wheat amylase inhibitor revealed 2:1 stoichiometric ratio and much more complex interaction with HaAmy1. Conclusions: The diversity of amylases in perspective of their biochemical and biophysical properties, and their differential interactions with amylase inhibitors signify the potential role of these enzymes in adaptation of H. armigera on diverse plant diets. General significance: Characterization of digestive enzymes of H. armigera provides the molecular basis for the polyphagous nature and thus could assist in designing future strategies for the insect control. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: alpha-amylases; Amylase inhibitors; Digestive enzymes; Enzyme activity; Helicoverpa armigera

Characterization of two coleopteran alpha-amylases and molecular insights into their differential inhibition by synthetic alpha-amylase inhibitor, acarbose - Channale, Sonal M.; Bhide, Amey J.; Yadav, Yashpal; Kashyap, Garima; Pawar, Pankaj K.; Maheshwari, V. L.; Ramasamy, Sureshkumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2016)
Post-harvest insect infestation of stored grains makes them unfit for human consumption and leads to severe economic loss. Here, we report functional and structural characterization of two coleopteran alpha-amylases viz. Callosobruchus chinensis alpha-amylase (CcAmy) and Tribolium castaneum alpha-amylase (TcAmy) along with their interactions with proteinaceous and non-proteinaceous alpha-amylase inhibitors. Secondary structural alignment of CcAmy and TcAmy with other coleopteran alpha-amylases revealed conserved motifs, active sites, di-sulfide bonds and two point mutations at spatially conserved substrate or inhibitor binding sites. Homology modeling and molecular docking showed structural differences between these two enzymes. Both the enzymes had similar optimum pH values but differed in their optimum temperature. Overall, pattern of enzyme stabilities were similar under various temperature and pH conditions. Further, CcAmy and TcAmy differed in their substrate affinity and catalytic efficiency towards starch and amylopectin. HPLC analysis detected common amylolytic products like maltose and maltotriose while glucose and malto-tetrose were unique in CcAmy and TcAmy catalyzed reactions respectively. At very low concentrations, wheat alpha-amylase inhibitor was found to be superior over the acarbose as far as complete inhibition of amylolytic activities of CcAmy and TcAmy was concerned. Mechanism underlying differential amylolytic reaction inhibition by acarbose was discussed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Acarbose; alpha-amylase; alpha-amylase inhibitor; Callosobruchus chinensis; Coleoptera; Tribolium castaneum

Genomic and functional characterization of coleopteran insect-specific alpha-amylase inhibitor gene from amaranthus species - Bhide, Amey J.; Channale, Sonal M.; Yadav, Yashpal; Bhattacharjee, Kabita; Pawar, Pankaj K.; Maheshwari, V. L.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Plant Molecular Biology, 2017)
The smallest 32 amino acid alpha-amylase inhibitor from Amaranthus hypochondriacus (AAI) is reported. The complete gene of pre-protein (AhAI) encoding a 26 amino acid (aa) signal peptide followed by the 43 aa region and the previously identified 32 aa peptide was cloned successfully. Three cysteine residues and one disulfide bond conserved within known alpha-amylase inhibitors were present in AhAI. Identical genomic and open reading frame was found to be present in close relatives of A. hypochondriacus namely Amaranthus paniculatus, Achyranthes aspera and Celosia argentea. Interestingly, the 3'UTR of AhAI varied in these species. The highest expression of AhAI was observed in A. hypochondriacus inflorescence; however, it was not detected in the seed. We hypothesized that the inhibitor expressed in leaves and inflorescence might be transported to the seeds. Sub-cellular localization studies clearly indicated the involvement of AhAI signal peptide in extracellular secretion. Full length rAhAI showed differential inhibition against alpha-amylases from human, insects, fungi and bacteria. Particularly, alpha-amylases from Helicoverpa armigera (Lepidoptera) were not inhibited by AhAI while Tribolium castaneum and Callosobruchus chinensis (Coleoptera) alpha-amylases were completely inhibited. Molecular docking of AhAI revealed tighter interactions with active site residues of T. castaneum alpha-amylase compared to C. chinensis alpha-amylase, which could be the rationale behind the disparity in their IC50. Normal growth, development and adult emergence of C. chinensis were hampered after feeding on rAhAI. Altogether, the ability of AhAI to affect the growth of C. chinensis demonstrated its potential as an efficient bio-control agent, especially against stored grain pests.

Glycoprotein alpha-amylase inhibitor from Withania somnifera differentially inhibits various alpha-amylases and affects the growth and development of Tribolium castaneum - Kasar, Sainath S.; Marathe, Kiran R.; Bhide, Amey J.; Herwade, Abhijeet P.; Giri, Ashok P.; Maheshwari, Vijay L.; Pawar, Pankaj K. (PEST Management Science, 2017)
BACKGROUND: Identification and characterisation of plant defensive molecules enrich our resources to design crop protection strategies. In particular, plant-derived proteinaceous inhibitor(s) of insect digestive enzymes appear to be a safe, sustainable and attractive option. RESULTS: A glycoprotein having non-competitive alpha-amylase inhibitory activity with a molecular weight of 8.3 kDa was isolated and purified from seeds of Withania somnifera alpha-amylase inhibitor (WSAI). Its mass spectrometry analysis revealed 59% sequence coverage with Wrightide II-type alpha-amylase inhibitor from Wrightia religiosa. A dose-dependent inhibition of alpha-amylases from Aspergillus oryzae, Bacillus subtilis, Helicoverpa armigera and Tribolium castaneumwas recorded. Interestingly, WSAI did not inhibit human salivary alpha-amylase significantly. When adults of T. castaneum were fed with WSAI (1.6mg g(-1)), decrease inconsumption, growthandefficiency of conversion of ingested foodwas evident, along withover fourfold increases in feedingdeterrence index. Adecline inlarval residual alpha-amylase activity after feedingofWSAI resulted ina reduction in longevity of T. castaneum. CONCLUSION: The study reflects the significance of WSAI in affecting the overall growth and development of T. castaneum. Pre-and post-harvest pest resistive capability makes WSAI a potential candidate for insect pest management. Further, the effectiveness of this inhibitor could be explored either in formulations or through a transgenic approach. (C) 2016 Society of Chemical Industry

Potent chitin-hydrolyzing enzyme from Myrothecium verrucaria affects growth and development of Helicoverpa armigera and plant fungal pathogens - Vidhate, Ravindra P.; Bhide, Amey J.; Gaikwad, Sushama M.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2019)
Chitin, a crucial structural and functional component of insects and fungi, serves as a target for pest management by utilizing novel chitinases. Here, we report the biocontrol potential of recombinant Myrothecium verrucaria endochitinase (rMvEChi) against insect pest and fungal pathogens. A complete ORF of MvEChi (1185 bp) was cloned and heterologously expressed in Escherichia coli. Structure based sequence alignment of MvEChi revealed the presence of conserved domains SXGG and DXXDXDXE specific for GH-18 family, involved in substrate binding and catalysis, respectively. rMvEChi (46.6 kDa) showed optimum pH and temperature as 7.0 and 30 degrees C, respectively. Furthermore, rMvEChi remained stable within the pH range of 6.0 to 8.0 and up to 40 degrees C. rMvEChi exhibited k(cat)/K-m values of 129.83 x 10(3) [(g/L)(-1) s(-1)] towards 4MU chitotrioside. Hydrolysis of chitooligosaccharides with various degrees of polymerization (DP) using rMvEChi indicated the release of DP2 as main end product with order of reaction as DP6 > DP5 > DP4 > DP3. Bioassay of rMvEChi against Helicoverpa armigera displayed potent anti-feedant activity and induced mortality. In vitro antifungal activity against plant pathogenic fungi (Ustilago maydis and Bipolaris sorokiniana) exhibited significant inhibition of mycelium growth. These results suggest that MvEChi has significant potential in enzyme-based pest and pathogen management. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Biocontrol; endochitinase; Myrothecium verrucaria

Mobile RNAs and proteins: impacts on plant growth and productivity - Kondhare, Kirtikumar R.; Bhide, Amey J.; Banerjee, Anjan K. (Journal of Experimental Botany, 2025)
Short- and long-distance mobile signals (mobile RNAs and proteins) are integral parts of the local and systemic communications that coordinate various physiological processes at the whole-plant level and have far-reaching impacts on plant productivity. In this review, we aim to provide a comprehensive description of the integral roles of these mobile signals in controlling phenotypic traits and plant productivity. We describe how key mobile RNAs (mRNAs, small RNAs, and long non-coding RNAs) and proteins (including RNA-binding proteins) function as vital regulators of multi-faceted aspects of phenotypic traits that ultimately govern plant productivity, such as the formation of the shoot apical meristem, leaf morphology, root architecture, flowering, ripening of fleshy fruits, tuberization, crop yield, and abiotic stress responses. We also describe recent advances in the study of macromolecular transport mechanisms, such as cyclophilin-mediated transport and extracellular vesicle-based signal delivery, as well as the identification of novel signature motifs on mobile RNAs. In addition, we consider the discovery of new mobile signals and highlight how these signals can potentially be explored with advanced biotechnological interventions, virus-induced flowering, genome-editing tools, and emerging breeding approaches (e.g. the xenia-based mobile RNA delivery system for fleshy fruits) with the aim of designing strategies for enhancing valuable phenotypic traits and improving plant productivity. Mobile RNAs and proteins act as key regulators of shoot apical meristem development, leaf morphology, root architecture, flowering, fleshy fruit ripening, tuberization, yield, and responses to abiotic stresses in plants.
Keywords: Long non-coding RNA; mobile protein; mobile RNA; plant productivity; RNA-binding protein; small RNA